Прагматичний контент біблійного тексту - Закреницька, Л. (Філологічний дискурс, 2018)
У статті розглянуто специфіку прагматики біблійного тексту з
урахуванням відмінності антропоцентризму від теоцентризму
християнського світогляду, окреслено зміст поняття християнсько-
теологічний антропоцентризм. Рецепція прагматики біблійного
тексту ґрунтується на взаємодії людського фактора з
Божественним. З’ясовано, що іллокуція та перлокуція в біблійному
тесті не спрямовані на підкорення людської волі та позбавлені ознаки
маніпуляції. Прагматика біблійного тексту розкривається через
контекст аналізованої мовленнєвої події. Виокремлено та
проаналізовано різні мовленнєві акти, визначено їхні домінантні види. The article deals with the specificity of the Biblical text pragmatics allowing for
the difference between the anthropocentrism and theocentrism of the Christian
outlook, also the content of the concept of Christian theological anthropocentrism is
outlined. The reception of pragmatics of the biblical text is based on the interaction
of the human factor with the Divine one. It has been found that components of
speech acts illocution and perlocution in the Bible test are not aimed at subjugation
of human will and void of any sign of manipulation.
The pragmatics of biblical text is revealed through the context of the analyzed
speech event. The typology of contexts is analyzed, the macrocontext and the context
of situation are emphasized as the prerogative of pragmatics. On the material of the
English version of the book «The Gospel of Luke» different speech acts are singled
out and analyzed, and as a result their dominant species are recognized to be
representatives, directives and commissives.